Synthesis and Biological Evaluation of a Novel Series of Pyrazolylcoumarins as Anti-Inflammatory and Antioxidant Agents - Aragade, P.; Venkatnarayanan, R.; Patil, P. (Drug Research, 2013)
A new series of pyrazolylcoumarins (4a-k) was synthesized by reaction of appropriate dibromochalcones (3a-k) with phenyl hydrazine in ethanol. Structures of all new synthesized compounds were characterized on the basis of elemental analysis and spectral data (UV, IR and 1H NMR). The title compounds were screened for in vivo anti-inflammatory activities at a dose of 200 mg/kg b.w. Among the 11 prepared compounds, Compounds 4c, d, h and i exhibited significant anti-inflammatory activity in model of acute inflammation such as carrageenan-induced rat edema paw while compound 4d showed considerable activity in model of chronic inflammation such as adjuvant-induced arthritis along with minimum ulcerogenic index and were compared with diclofenac (13.5 mg/kg b.w.) as a standard drug. Additionally, the synthesized compounds were evaluated for their in vitro antioxidant activity. Compound 4k was found to be the most active antioxidant in the series compared with standard vitamin C.
Keywords: DPPH; coumarin; NSAIDs; pyrazole